Métodos activos y su incidencia en el proceso de aprendizaje de los estudiantes de educación básica media de la Escuela Bolívar Guarderas, Cantón Buena Fe, Provincia de los Ríos - Chuez Espinal, Evelin Lissette (2016)
This project aims to redesign the incidence of active methods in the learning process of students, linking scientific and technological content. To do this, first, we proceeded to conduct research on the level with students of Basic Education Middle School Bolivar Education Guarderas in the process of learning to determine what degree of comprehensive development have to develop the various school activities and life in the future. The theoretical framework discusses the general concepts and dimensions that conform achieve excellence in this project. The research methodology is descriptive, explanatory and participatory. Carried out through a process of collecting information through surveys involved (teachers and students). These being subjected to a statistical tabulation process. Concluding that students of Basic Education Media of that school known active methods, it does not allow them to develop their own educational activities entrusted. Recommending implement a tutorial activities in order to create new expectations for teachers and students Bolivar School Guarderas, it is expected that this project is very useful for students because a good application of active methods, achieved a good development in their educational activities and allow them to perform as a thinking citizen, confident and able to solve problems and understand the surrounding environment